Microstructure and the dielectric properties of Eu and Co CO-DOPED BiFeQ3 / Tuan Syarifah Nurul Hanani Syed Ahmad - Syed Ahmad, Tuan Syarifah Nurul Hanani (2012)
Pure BiFe03, Eu doped BiFeOs, and Eu and Co co-doped BiFe03. The BiFe03, Bii.xEuxFe03 and Bii.xEuxFei.yCoy03 were successfully prepared by solid state reaction method with (x = 0.1, 0.15, 0.2 and y = 0.1, 0.15). The effects of the doped and co-doped was studies on dielectric properties of BiFe03, Bii_xEuxFe03 and Bii_ xEuxFei.yCoy03 samples have been studied by performing x-ray diffraction (XRD), scanning electron microscopy (SEM) and dielectric measurement by electrical impedance spectroscopy (EIS). The results of the samples Bii.xEuxFe03 and Bij. xEuxFei.yCoy03 are compared to the pure bismuth ferrite (BiFeOs). XRD results confirm the formation of BiFe03 as major phase with secondary phase when codoped with Co. The SEM indicated that the sizes of the crystalline of the samples were decreased with increases of concentrations of the Eu and Co doped in the samples. Co-doping of the sample is smallest crystalline size and the pure sample is the most large crystalline size except for the y = 0.1. Dielectric measurement is done for all the samples. The low frequency dielectric constant and dielectric loss of samples decreases with increase in frequency. The sample of codoping Eu and Co in BiFe03 showed largest dielectric constant and smallest dielectric loss values compared to the pure BiFe03.